The Medicinal Chemistry of Chalcones as Anti-Mycobacterium tuberculosis Agents - Rodríguez-Silva, Cristhian N.; Prokopczyk, Igor Muccilo [UNESP]; Dos Santos, Jean Leandro [UNESP] (Bentham Science Publishers, 2022)
Tuberculosis (TB), a highly fatal infectious disease, is caused by Mycobacterium tuberculosis (Mtb) that has inflicted mankind for several centuries. In 2019, the staggering number of new cases reached 10 million resulting in 1.2 million deaths. The emergence of multidrug-resistanceMycobacterium tuberculosis (MDR-TB) and extensively drug-resistant-Mycobacterium tuberculosis (XDR-TB) is a global concern that requires the search for novel, effective, and safer short-term therapies. Nowadays, among the few alternatives available to treat resistant-Mtb strains, the majority have limitations, which include drug-drug interactions, long-term treatment, and chronic induced toxicities. Therefore, it is mandatory to develop new anti-Mtb agents to achieve health policy goals to mitigate the disease by 2035. Among the several bioactive anti-Mtb compounds, chalcones have been described as the privileged scaffold useful for drug design. Overall, this review explores and analyzes 37 chalcones that exhibited anti-Mtb activity described in the literature up to April 2021 with minimum inhibitory concentration (MIC90) values inferior to 20 µM and selective index superior to 10. In addition, the correlation of some properties for most active compounds was evaluated, and the main targets for these compounds were discussed.
Keywords: 1,3-Diphenylpropenones; antitubercular drugs; chalcones; chalconoids; medicinal chemistry; Mycobacterium tuberculosis H37Rv; Mycobacterium tuberculosis infection; pharmaceutical design